Aplikasi Monitoring Work Order Request Berbasis Client Server di PT. Sanden Electronics Indonesia - Zulkipli, Zulkipli; Felany, Felany (LPPM Sekolah Tinggi Teknologi Indonesia Tanjung Pinang, 2023)
In the last decade, the interest of researchers to develop technology has increased rapidly. In an industrial context, the use of technology can help increase a company's business potential. In making a list of raw materials at PT. Sanden Electronics Indonesia, the logistics department has not used an application specifically to handle monitoring of raw material picking and to connect between officers/makers of raw material lists and supervisors. The manual data collection process based on the case study was considered too slow. Based on these problems, the researcher took the initiative to develop a product in the form of a client server-based work request monitoring application and to conduct application testing at PT. Sanden Electronics Indonesia. This research was conducted using the Research & Development (R&D) method and the development of the software used in developing this application used the Spiral Model. Based on the results of application testing that has been carried out in the form of testing the input login form, work order request, tube master list testing, tube stock code testing, as well as testing the monitoring status input form, the product is a client server-based monitoring application developed using the Java programming language using Netbeans IDE, can be implemented well in PT. Sanden Electronics Indonesia.